Consumption of acai (Euterpe oleracea Mart.) functional beverage reduces muscle stress and improves effort tolerance in elite athletes: a randomized controlled intervention study - Carvalho-Peixoto, J.; Moura, M. R. L.; Cunha, F. A.; Lollo, P. C. B.; Monteiro, W. D.; de Carvalho, L. M. J.; Farinatti, P. de T. V. (Applied Physiology, Nutrition, and Metabolism, 2015)
The study analyzed the effect of an açai (Euterpe oleracea Mart.) functional beverage (AB) on muscle and oxidative stress markers, cardiorespiratory responses, perceived exertion, and time-to-exhaustion during maximal treadmill running. The beverage was developed as an ergogenic aid for athletes and contained 27.6 mg of anthocyanins per dose. Fourteen athletes performed 3 exercise tests: a ramp-incremental maximal exercise test and 2 maximal exercise bouts performed in 2 conditions (AB and without AB (control)) at 90% maximal oxygen uptake. Blood was collected at baseline and after maximal exercise in both conditions to determine biomarkers. AB increased time to exhaustion during short-term high-intensity exercise (mean difference: 69 s, 95% confidence interval = -296 s to 159 s, t = 2.2, p = 0.045), attenuating the metabolic stress induced by exercise (p < 0.05). AB also reduced perceived exertion and enhanced cardiorespiratory responses (p < 0.05). The AB may be a useful and practical ergogenic aid to enhance performance during high-intensity training.